Destination Management: Nepalese Efforts, Experiences & Challenges - Neupane, Prakash Chandra (The Gaze: Journal of Tourism and Hospitality, 2019)
Nepal with diverse geographical landscapes, rivers, mountains and alluring religious and cultural sites, has been declared as top first destination amongst various global destinations. Standardized destination management efforts with designated entities has not gone satisfactorily as expected, resulting poor inbound tourism in Nepal. This article will go around the various initiatives taken for the destination management from both government and non-government level and their implications for successful ecotourism practices in Nepalese perspective. Ideal destination management is all about providing convincing safety and security, logistics, entertainment, health and sanitation and much other to the tourists.